Prevalence of Menstrual Cycle Disorders in Injectable Contraceptive Acceptors: Study at Mulya Mekar Health Center, Purwakarta Regency, Indonesia - Lusianawati, Evalina Fransisca (Archives of The Medicine and Case Reports, 2024)
Injection contraception is a hormonal contraceptive method that is widely used by women in Indonesia. This method has the advantages of high effectiveness and ease of use. However, contraceptive injections can also cause side effects, one of which is menstrual cycle disorders. This study aims to determine the prevalence of injection contraceptive acceptors on the menstrual cycle at the Mulya Mekar Health Center, Purwakarta Regency, Indonesia. This research uses a descriptive observational research design with accidental sampling. The research sample was 50 contraceptive injection acceptors aged 15-49 years. Data was collected using a questionnaire. The research results show that the prevalence of injection contraceptive acceptors who experience menstrual cycle disorders is 60%. The most frequently experienced menstrual cycle disorders are longer menstrual cycles (26%), followed by shorter menstrual cycles (24%), and irregular menstrual cycles (10%). This study concludes that the prevalence of menstrual cycle disorders in recipients of contraceptive injections is quite high. Therefore, it is important for acceptors to know the risks and benefits of this contraceptive method.